Abundant closed-form solitons for time-fractional integro–differential equation in fluid dynamics - Az-Zo’bi, Emad A.; AlZoubi, Wael A.; Akinyemi, Lanre; Şenol, Mehmet; Alsaraireh, Islam W.; Mamat, Mustafa (Optical and quantum electronics, 2021)
In this paper, with the aid of the Mathematica package, several classes of exact analytical solutions for the time-fractional ( 2 + 1 ) -dimensional Ito equation are obtained. To analytically tackle the above equation, the Kudryashov simple equation approach and its modified form are applied. Rational, exponential-rational, periodic, and hyperbolic functions with a number of free parameters were represented by the obtained soliton solutions. Graphical illustrations with special choices of free constants and different fractional orders are included for certain acquired solutions. Both approaches include the efficiency, applicability and easy handling of the solution mechanism for nonlinear evolution equations that occur in the various real-life problems.